The Impact of Viral Marketing and Destination Image on Visiting Intentions to Semarang City During The Covid-19 Pandemic - Firdaus; Rusmiyatun; Jatmiko, Muhamad Roby (International Publisher (YAPENBI), 2022)
This study aims to explain the relationship between viral marketing and destination image variables on the intention to visit the city of Semarang. The sample in this study was 100 respondents. In comparison, the implementation of sampling in this study uses an accidental sampling technique, namely the technique of taking samples by chance from the respondents. The data analysis technique used multiple regression. The results of statistical tests concluded that (1) there is a positive and significant relationship between viral marketing and the intention to visit, which means that the higher the viral marketing in a city, the higher the intention to visit, and the second result (2) there is a correlation which is positive and significant between destination image and intention to visit, meaning that the better the destination image, the higher the intention to visit made by consumers to visit the city of Semarang. Conversely, the worse the viral marketing and destination image of consumers, the lower the intention to visit made by consumers. Findings : This research proves that with viral content and a good image of a tourist destination, it can make tourists interested in visiting the city of Semarang.